2013
DOI: 10.1177/0969733012475253
|View full text |Cite
|
Sign up to set email alerts
|

Aspects of indignity in nursing home residences as experienced by family caregivers

Abstract: The overall purpose of this cross-country Nordic study was to gain further knowledge about maintaining and promoting dignity in nursing home residents. The purpose of this article is to present results pertaining to the following question: How is nursing home residents' dignity maintained, promoted or deprived from the perspective of family caregivers? In this article, we focus only on indignity in care. This study took place at six different nursing home residences in Sweden, Denmark and Norway. Data collecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
77
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 42 publications
(79 citation statements)
references
References 39 publications
1
77
0
1
Order By: Relevance
“…This understanding reduces vulnerability to the functioning body regardless of the psycho-socio-cultural context the residents are in, and it ignores the role of the nursing home environment. From a family carers´ perspective of dignity, vulnerability was experienced as a feeling of being abandoned (Nåden et al 2013). In an illness context of dignity, it was shown that vulnerability is an issue of functional incapacity (Oosterveld-Vlug et al 2013a).…”
Section: Figure 1 To Be Insertedmentioning
confidence: 99%
“…This understanding reduces vulnerability to the functioning body regardless of the psycho-socio-cultural context the residents are in, and it ignores the role of the nursing home environment. From a family carers´ perspective of dignity, vulnerability was experienced as a feeling of being abandoned (Nåden et al 2013). In an illness context of dignity, it was shown that vulnerability is an issue of functional incapacity (Oosterveld-Vlug et al 2013a).…”
Section: Figure 1 To Be Insertedmentioning
confidence: 99%
“…As our findings show, residents living in nursing homes may experience all these types of threat in the care-relationship. This result is also supported by findings from interviews with family members on how they experience the care for their loved ones in nursing homes (Nåden et al, 2013).Their loved one may be seen as a number within a group, the resident group. Their personal space may be violated every day when the care workers help the old and frail person with daily care, which is often of an intimate character.…”
Section: Dignity and Institutional Frames From The Perspective Of A Rmentioning
confidence: 53%
“…18 Dignity has been defined in many different ways and the model presented by Nordenfelt is often referred to as providing a comprehensive definition of the concept. 3,6,8,[18][19][20][21][22] Nordenfelt's four notions are as follows:…”
Section: Nordenfelt's Four Notions Of Dignitymentioning
confidence: 99%
“…3 Of the literature reviewed on the subject, eight authors agree that it is easier to describe undignified care. [3][4][5][6][7][8][9][10] There have also been suggestions that dignity is a vague and nebulous concept detached from the reality of care delivery.…”
Section: Introductionmentioning
confidence: 99%